Design de TICS para apoiar fisioterapeutas em um hospital de doenças mentais crônicas - Silvestre, Rodrigo Gustavo (2013)
The use of computing technologies to support healthcare processes has already been used for decades. More recently, the natural user interfaces (NUI) has been used to assist these processes, especially in therapeutic treatments. The UNITY Project, in which this work is part of, aims to explore the adoption of NUI to support professionals working in a hospital that treats chronic mental illness. The specific problem that this research addresses is to identify how information and communication technologies can be used to support, naturally, the work routine of health professionals who work in long-term care of patients with chronic mental illness. During several months of field research activities involving researchers and health professionals were developed for design, using more traditional approaches in the field of Human-Computer Interaction (HCI) as participatory design and user-centered design, as well as more recent proposals such as design for appropriation. After a long iterative process and several rounds of prototyping, it was possible to design a digital system that allows health professionals to register, view and share information about their patients, thereby contributing to the creation of a digital record of the patients and the outcome and results of the treatments applied in them. The design process was centered in the health professional taking into consideration the information and features that support them in their work routine. Thus, results from this work was the beginning of an identification of a health care centered design model and the impact that this approach has on the final result arising from this process.